Involvement of cdks and cyclins in muscle differentiation - M De Falco; A De Luca (European Journal of Histochemistry, 2009)
Myocyte differentiation is due to transcription of genes that characterize the phenotypic and biochemical identity of differentiated muscle cells. These are the myogenic regulatory factors (MRFs) MyoD, Myf5, myogenin and MRF4. Overexpression of cdk/cyclins has been reported to inhibit the activity of MyoD and prevent myogenic differentiation by different modalities. Unlike other cdk/cyclin complexes, overexpression of cdk9/cyclin T2a, enhances MyoD function and promotes myogenic differentiation. In addition, cyclin T2a interacting with a novel partner, PKNa, is able to strongly enhance the expression of myogenic differentiation markers, such as myogenin and Myosin Heavy Chain. So, cyclin T2a could stimulate myogenic differentiation interacting with different kinase partners Cdk9 or PKNa in a synergistic or antagonistic way.